Tracing the Genealogy of MaqÄá¹£id al-SharÄ«'ah Concept: A Historical Approach - Tajrid, Amir (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This paper aims to explore the emergence, continuity and shifting of the meaning of maqÄá¹£id al-sharÄ«â€™ah. Initially, maqÄá¹£id al-sharÄ«â€™ah entered into the study of uá¹£Å«l al-fiqh and later became an independent scientific discipline. Historically, the journey of maqÄá¹£id al-sharÄ«â€™ah has four periods, namely, the pre-codification era, the first development era, the second development era, and the maturation era as a scientific discipline. This paper is qualitative with a descriptive-analytic method, namely exploring the concept of maqÄá¹£id al-sharÄ«â€™ah in various literature. The findings in this paper are, first, the history of the emergence and development of maqÄá¹£id al-sharÄ«â€™ah is closely related to the enforcement of Islamic law. Second, the continuity of maqÄá¹£id al-sharÄ«'ah is an ideological concept because it is based on the prevailing paradigm